Hubungan Beban Kerja dengan Work Life Balance pada Perawat di Rumah Sakit - Wanda Aprilyasari; Fitriyatus Sholikha; Irvan Ardiansyah; Moch Abdillah Islami; Suratmi Suratmi; Nurul Hikmatul Qowi (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
Work life balance is a problem experienced by health workers, one of which is in the nurse group. Nurses are faced with high role demands, where the tasks and responsibilities of activities that need to be completed at the same time, this will cause an imbalance in their personal lives. The purpose of this study was to determine the relationship between workload and work-life balance in nurses at the hospital. This correlation research design uses a crossectional approach. The research sample taken using total sampling amounted to 41 nurses. The research data was taken with a questionnaire sheet, then analyzed using the Spearman Rho test. The results showed that most (63.4%) nurses experienced heavy workload, and most (56,1%) nurses experienced currently work-life balance. Based on the results of the analysis using an ordinal scale with the Spearman Rho test, the p value = 0.000 (p <0.05) and the value = ─0.517, then H1 is accepted. There is a relationship between workload and work life balance in nurses at the hospital. Based on the results of the study, it is hoped that the hospital will pay attention in handling the tasks and responsibilities experienced by nurses so that nurses are able to manage time in completing their work to be maximized and directed without thinking about matters outside of their work.